"Prevention Alone Is Not Enough:" Stakeholders’ Perspectives About School-based Child Sexual Abuse (CSA) Prevention Programs and CSA Research in China - Lu, Mengyao (Journal of interpersonal violence, 2022)
While existing studies have examined the effectiveness of school-based child sexual abuse (CSA) prevention programs in China, there is currently little qualitative evidence on how stakeholders view these programs and research on CSA in China more generally. To address this research gap, the aims of this study were to explore stakeholders? perspectives on: (a) school-based CSA prevention programs in China; (b) the components of these programs; (c) CSA research in China. Qualitative semi-structured interviews were conducted with 21 participants in Beijing and a county under Lanzhou City, China. Interview transcripts were systematically coded and emerging themes were developed from the codes. An inductive thematic analysis approach was utilized to analyze the interview data. Participants? perspectives on school-based CSA prevention programs included: (a) recognition of the importance of school-based CSA prevention programs; (b) fear about a possible negative impact on children participating in such programs; (c) assessment that school-based CSA prevention programs alone are not enough to prevent CSA. Components that participants thought needed to be part of Chinese school-based CSA prevention programs were: (a) content regarding online-facilitated CSA; (b) the use of a rights-based approach; and (c) greater parental and community involvement. Participants also identified factors that have both fostered the implementation of CSA research (e.g., the growing awareness of CSA in the central government) and prevented researchers from effectively conducting CSA research: (a) lack of national data; (b) inadequate government support; and (c) barriers to research collaboration among organizations. The findings indicate that while CSA prevention programs are on the whole regarded positively by key stakeholders in China, a number of important concerns were identified. Our study highlighted a number of ways in which future CSA prevention programs and research on CSA could be strengthened in the Chinese context.